Effect of Integral Waterproofing on Strength and Durability of Foamed Concrete - Jack Widjajakusuma; Ricky Tjahjono; Muhammad Agil Faisal; Mainawa Bidangan (Institute of Advanced Knowledge and Science, 2026)
Foamed concrete is widely used in lightweight construction, but its porous structure leads to high water absorption and moisture damage, thereby limiting durability. This study examines how an integral waterproofing admixture affects density, compressive strength, and internal quality of foamed concrete produced by the pre-formed foam method. Five mixes were tested: two references with polycarboxylate superplasticizer at two foam levels (2F3-S, 2F5-S) and three with the admixture at 5, 7.5, and 10 kg/m³ (2F3A5, 2F3A7.5, 2F3A10). Density, compressive strength (at 1, 3, 7, and 28 days), and ultrasonic pulse velocity (UPV) were measured. Waterproofed mixes showed higher 28-day density (1911–2020 kg/m³) and strength (34.4–43.0 MPa) than references (1665 kg/m³, 21.9 MPa). Strength rose with admixture dosage. Early-age strengths were similar, so hydration was not hindered. Higher density suggests admixture–foam interaction. At 28 days, UPV was higher in waterproofed mixes (4.3–4.5 km/s vs. 2.8–3.3 km/s) and closely correlated with density (R² = 0.99), indicating better cohesion and less pore connectivity. The high-foam reference mix had only 8.5 MPa at 1463 kg/m³, showing the strength loss from more foam. Thus, integral waterproofing improves foamed concrete’s quality and is effective for moisture-exposed elements like façade panels, roofs, and lightweight components, offering an alternative to surface waterproofing.